Culture, work, and psychology : invitations to dialogue - Bendassolli, Pedro F. (Advances in cultural psychology., 2019)
This books arises from the observation that mainstream psychology, especially work and organisational psychology (WOP), suffers from critical limitations in its attempts to deal with the complexities of work as a cultural phenomenon. We can only mention a few examples here. In the WOP field, especially in Anglo- Saxon tradition, work experiences are seen through the lenses of traditional behavioural approaches, whereas culture is seen as a 'software of the mind', to use a popular definition found in this field (based on cross-cultural mainstream psychology). 'Competences', to take another example, are thought of as something that do or do not people have inside them. Suffering, like stress (a common work-based problem of our times), is considered to be dependent on a person's personality, perceptions or as a set of behaviours triggered by facing an 'objective' environment. Even meaning-making process can be found to be defined from a WOP mainstream point of view: meanings are 'social cognitions' shared by people by means of unidirectional socialisation processes.Therefore, the goal of this book is to deliver to the reader a new and challenging theoretical and methodological tool box, inspired by insights developed from a broad cultural psychological perspective. Its focus is on the consideration of work and organisations based on core concepts developed inside cultural psychology. Therefore, it is designed to discuss potential extensions of these concepts to work psychology.